Judicial Decisions in Federal Decree-Law No. 15 of 2021 - Alsandal, Mariam (Journal of Legal Sciences, 2022)
Judges perform many acts in the exercise of their function and issue many judicial rulings, judicial decisions, in addition to judicial orders; Accordingly, judicial decisions differ from judicial decisions, and both differ from judicial orders. Although judicial rulings and judicial orders are clear and their nature can be accurately identified, defining judicial decisions, especially those added by the legislator in the UAE under Federal Decree Law No. 15 of 2021, is not that easy. In the aforementioned decree-law, the Emirati legislator added the word (Decision) with each word (Ruling) in most of the legal texts subject to amendment under this decree.Judicial decisions issued by judges during the exercise of their functions are numerous and varied, and not all of them are subject to the rules contained in Federal Decree-Law No. 15 of 2021, but rather the legislator singled out a specific type of judicial decisions, and although they are not explicitly specified in the decree, we can infer them from Through the texts of Civil Procedures Law No. 11 of 1992 and its amendments, and Regulation No. 57 of 2018 and its amendments.